Autism-associated familial microdeletion of Xp11.22 - Qiao, Y; Liu, X; Harvard, C; Hildebrand, MJ; Rajcan-Separovic, E; Holden, JJA; Lewis, MES (Clinical genetics, 2008)
We describe two brothers with autistic disorder, intellectual disability (ID) and cleft lip/palate with a microdeletion of Xp11.22 detected through screening individuals with autism spectrum disorders (ASDs) for microdeletions and duplications using 1‐Mb resolution array comparative genomic hybridization. The deletion was confirmed by fluorescence in situ hybridization/real‐time quantitative polymerase chain reaction (RT‐qPCR) and shown to be inherited from their unaffected mother who had skewed (100%) X inactivation of the aberrant chromosome. RT‐qPCR characterization of the del(X)(p11.22) region (∼53,887,000–54,359,000 bp) revealed complete deletion of the plant homeodomain finger protein 8 (PHF8) gene as well as deletions of the FAM120C and WNK lysine‐deficient protein kinase 3 (WNK3) genes, for which a definitive phenotype has not been previously characterized. Xp11.2 is a gene‐rich region within the critical linkage interval for several neurodevelopmental disorders. Rare interstitial microdeletions of Xp11.22 have been recognized with ID, craniofacial dysmorphism and/or cleft lip/palate and truncating mutations of the PHF8 gene within this region. Despite evidence implicating genes within Xp11.22 with language and cognitive development that could contribute to an ASD phenotype, their involvement with autism has not been systematically evaluated. Population screening of 481 (319 males/81 females) and 282 X chromosomes (90 males/96 females) in respective ASD and control cohorts did not identify additional subjects carrying this deletion. Our findings show that in addition to point mutations, a complete deletion of the PHF8 gene is associated with the X‐linked mental retardation Siderius‐Hamel syndrome (OMIM 300263) and further suggest that the larger size of the Xp11.22 deletion including genes FAM120C and WNK3 may be involved in the pathogenesis of autism.